1995
DOI: 10.1073/pnas.92.24.11100
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model for Usher syndrome: linkage mapping suggests homology to Usher type I reported at human chromosome 11p15.

Abstract: Usher syndrome is a group of diseases with autosomal recessive inheritance, congenital hearing loss, and the development of retinitis pigmentosa, a progressive retinal degeneration characterized by night blindness and visual field loss over several decades. The causes of Usher syndrome are unknown and no animal models have been available for study. Four human gene sites have been reported, suggesting at least four separate forms of Usher syndrome. We report a mouse model of type I Usher syndrome, rd5, whose li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 22 publications
3
50
0
Order By: Relevance
“…Bardet-Biedl syndrome is characterized by many systemic disorders, including retinal dystrophy or pigmentary retinopathy, which is accompanied by abdominal obesity and type 2 diabetes (Iannello et al, 2002). Mutations in the Tubby gene family reveal a relationship between retinal function and insulin action (Ikeda et al, 2002); mutations in the mouse Tubby gene causes obesity, deafness, and retinal photoreceptor degeneration (Heckenlively et al, 1995). In addition, mutations in tubby-like protein 1 (TULP1), a member of the human Tubby gene family, are associated with autosomal recessive retinitis pigmentosa (Banerjee et al, 1998;Hagstrom et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Bardet-Biedl syndrome is characterized by many systemic disorders, including retinal dystrophy or pigmentary retinopathy, which is accompanied by abdominal obesity and type 2 diabetes (Iannello et al, 2002). Mutations in the Tubby gene family reveal a relationship between retinal function and insulin action (Ikeda et al, 2002); mutations in the mouse Tubby gene causes obesity, deafness, and retinal photoreceptor degeneration (Heckenlively et al, 1995). In addition, mutations in tubby-like protein 1 (TULP1), a member of the human Tubby gene family, are associated with autosomal recessive retinitis pigmentosa (Banerjee et al, 1998;Hagstrom et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by an autosomal recessive gene on chromosome 1, at a totally different locus than the genes associated with the rd~Carter- Dawson et al, 1978!, Rds Sanyal et al, 1980!, pcd, nr~Mullen & LaVail, 1975!, mnd Chang et al, 1994!, tubby~Heckenlively et al, 1995Lamoreux et al, 1992!, rd6~Hawes et al, 2000 Mehalow et al, 2003!, or Rpe65 rd12~P ang et al, 2005generations in mice. Crossbreeding of rd-3/rd-3 mice with mice homozygous for the first six of these mutations produce unaffected offspring~Chang et al, 1993aoffspring~Chang et al, , 1994Heckenlively et al, 1995!. Preliminary studies using both morphological and electroretinogram~ERG! data showed a strong correlation between the time course of photoreceptor loss in each strain and the gradual extinction of the a-wave in each~Chang et al, 1993a; Heckenlively et al, 1993b; Nusinowitz et al, 1997!.…”
Section: Introductionmentioning
confidence: 99%
“…The tubby and rd5 mouse phenotypes display both retinal and cochlear degeneration and have been suggested as murine models for Usher syndrome, as these mutations map to distal mouse chromosome 7, which is partially syntenic to 11p15 (Heckenlively et al 1995;Ohlemiller et al 1995;Chung et al 1996). However, based on both genetic and physical mapping studies, a relationship with USH1C seems unlikely.…”
Section: Discussionmentioning
confidence: 95%